IMPLEMENTATION OF THE CITY WITHOUT SLUMS (KOTAKU) PROGRAM IN JOHOR VILLAGE BUILDING, MEDAN JOHOR DISTRICT - Raihan Suryani; Sally Marisa Sihombing (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
The KOTAKU program is a national program with clear goals and achievement targets that require funding sources that are complementary and timely. The KOTAKU Program aims to improve access to basic infrastructure and services in urban slum areas and support the realization of livable, productive and sustainable urban settlements. This research uses descriptive research methods with a qualitative approach. This is in line with the research objective to see how the KOTAKU program policy is implemented in dealing with the problem of slum areas in Medan Johor District. In this qualitative research method, researchers use the Van Horn Van meter implementation model which influences the implementation of public policy, namely: policy standards and targets, resources, inter-organizational relationships, characteristics of implementing agents, social, political, and economic conditions, and implementor dispositions. Based on the results of research that has been carried out, it shows that the City Without Slum Settlements (KOTAKU) program implemented in the Gedung Johor sub-district has not been fully effective and efficient because it has not yet reached the standards for infrastructure development and basic housing services as well as improving the welfare of urban communities.